Relation Between Body Mass Indexs And Menstrual Cycles In Undergradute Nursing Students At The Jombang Regency Government Institute Of Health Sciences - Anis Satus Syarifah; Dinar Rizqandany; Mamik Ratnawati; Sestu Retno Dwi Andayani; Rodiyah (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Menstruation is defined as a natural process that occurs within the female reproductive organs.Body mass index (BMI) is one of the factors that can affect the menstrual cycle. Body mass index is used as a measuring tool for monitoring nutritional status. A person is interpreted in three categories, namely thin, normal, and fat. Objective: to identify The results of this study aim to identify the relationship between body mass index and menstrual cycle in undergraduate nursing students at STIKES Pemkab Jombang Methods: This article : The design used in this study was a cross sectional design. The population studied consisted of 212 undergraduate nursing students at levels 1-3 at STIKES Pemkab Jombang. The sample taken amounted to 67 female students with Cluster Random Sampling technique. Data were collected through interviews and checklist filling Results: The results of this study showed that most (59.7%) respondents fell into the normal body mass index category and most (64.2%) respondents experienced a normal menstrual cycle. This study used the Spearman rank correlation test, with a p value = 0.001 < α = 0.05 and r = 0.620, so H0 was rejected. This indicates a positive correlation between body mass index and menstrual cycle in undergraduate nursing students at STIKES Pemkab Jombang Conclusion: Women with a normal body mass index (BMI) tend to have regular menstrual cycles. Conversely, a BMI that is too low or too high can trigger menstrual cycle irregularities. Therefore, maintaining weight and health is important for women